PENATA KAMERA DAN EDITING DALAM FILM DOKUMENTER "BHINNEKA TUNGGAL PERSIJA: SUARA THE JAKMANIA" - Muhammad Halbi Qastalany Syibli (2024)
This documentary aims to depict the emotional journey and organizational culture of The Jakmania, the largest football supporters group in Indonesia. The film reveals that The Jakmania are not just ordinary supporters, but also an integral part of the history of Indonesian football and a united society. The film depicts the fanaticism and deep love for the pride team, Persija Jakarta, the film reflects the influence of The Jakmania in diverse social contexts. The production process of this documentary uses camera work described through the work of a Cameraman. It also explains the role of the Editor who is no less important than the Cameramen have a big responsibility in creating the visual aspects of the movie from pre-production to post-production. They must have a strong vision of lighting and visual composition to help convey the film's story to the fullest. Effective collaboration with the production team, decision-making, and ensuring visual consistency are the main responsibilities of the Cameraman. Overall, the role of a Cameraman is crucial in the pre-production, production, and post-production stages of a documentary film, as it requires careful planning, careful supervision, and ensuring visual consistency during the editing process.